TEKNOLOGI TEPAT GUNA PENGOLAHAN LIMBAH PLASTIK MENJADI PAVING BLOCK SEBAGAI ALTERNATIF PEMECAHAN MASALAH SAMPAH TAHUN 2023 - Yasril, Abdi Iswahyudi; Nurdin, Nurdin; Alfarisi, Muhammad (Universitas Fort De Kock, 2024)
Waste remains a prevalent issue that has not been effectively addressed. In Indonesia, a significant portion of the population still views waste as useless residual material. The total waste generated in Indonesia reached 21.88 million tons in 2021, with households contributing the largest share at 42.23%, followed by businesses at 19.11%, markets at 15.26%, offices at 6.72%, public facilities at 6.71%, and other sources at 3.55%. This research is an experimental study utilizing a True Experiment design. The descriptive data analysis focuses on transforming plastic waste into paving blocks. Based on the research findings, plastic waste is a highly suitable material for making paving blocks because plastics contain fiber strands that bind the plastic with other materials. After testing for durability, it was discovered that plastic paving blocks can withstand loads of up to 87 kg and exhibit good water absorption properties. Paving blocks made from plastic waste fall into the quality classifications C and D. In conclusion, the production of paving blocks using a mixture of PET plastic involves several stages, including equipment and material preparation, waste collection, cutting, heating, molding, release, soaking, and drying. This process constitutes pure experimentation aimed at producing an alternative solution to waste management. It is recommended that the community can utilize this research by creating paving blocks from PET plastic waste